Email Spam Detection Using Machine Learning - Shaik Mohammed Fateen; Shaik Mohammad Asif; Shaik Afroz; N Mohammed Sami; Dr. Tippanna (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Email Spam has become a major problem nowadays, with Rapid growth of internet users, Email spams is also increasing. People are using them for illegal and unethical conducts, phishing and fraud. Sending malicious link through spam emails which can harm our system and can also seek in into your system. Creating a fake profile and email account is much easy for the spammers, they pretend like a genuine person in their spam emails, these spammers target those peoples who are not aware about these frauds. So, it is needed to Identify those spam mails which are fraud, this project will identify those spam by using techniques of machine learning, this paper will discuss the machine learning algorithms and apply all these algorithms on our datasets and best algorithm is selected for the email spam detection having best precision and accuracy.